Secure Enhanced Reactive Routing Protocol for Manet Using Two Fish Algorithm - Deepa, M; Krishna Priya, P (International Journal of Engineering and Technology, 2018)
In Mobile Adhoc Network (MANET) implementing a secure communication is a critical task due to its nature of wireless, infrastructureless, arbitrary network. Its not organized by any centralized control. Each node in this networkÂ Â acts as a router. Routing plays a major role in the network data transmission. Various protocols exist for the purpose of routing process. On Demand routing is a category of routing protocol were routes are obtained only on demand. AODV is one of the efficient on demand routing protocol. In this work an enhanced protocol with security features, the Secure AODV- ESB (Secure Adhoc On Demand Distance Vector based on Energy level and Signal Strength Implementing Bayesian Probability) has been proposed for MobileÂ Â Adhoc Network. Its is an extension of the previous work AODV â€“ ESB protocol, which is a modification of the existing AODV protocol. The AODV protocol works on two phases.Â The route discovery process and route maintenance phase. Major problem faced by AODV was the frequent route break caused by the dynamic mobile nature of the Mobile Adhoc network, which leads to frequent route discovery process. To avoid frequent route break AODV-ESB routing protocol was proposed, it adopts the energy level and Signal strength as parameters for the route selection for transmission of data. Bayesian probability implementation in the protocol increases the chance of adopting more reliable and optimized path. Another major issue in data transmission in the Adhoc network is the security. Securing data from access of the unauthorized person is a major responsibility of the protocol. This new secure AODV- ESB protocol protects against attackers by identifying the malicious node and eliminating them and also secures data by implementing cryptography using Two Fish Algorithm.Â This ensures secure data transmission in MANET more efficiently than the original AODV protocol. Analysis using the NS 2 Simulator proves that Secure AODV- ESB performs better than the previous work AODV- ESB.Â Â